The Common-Law Conception of Leasing: Mitigation, Habitability, and Dependence of Covenants - John A. Humbach (Washington University Law Quarterly, 1983)
In this Article, common-law conception of the landlord-tenant relation will be portrayed as a natural result of an interplay between basic law of property and of contract. This conception will be described by the rules and results which it implies and by the theories that underlie these rules. This will not be a historical account, though history must be mentioned. Neither will it be a complete account. A flood of specific applications would more likely obscure than elucidate the underlying conception which those applications imply and from which they can be seen to flow. Rather, the object here is to describe the basic conception itself. The hypothesis is that landlord-tenant law is in large part logically coherent and that most of the specific applications of landlord-tenant law follow from a basic conceptual framework. Thus, understanding the framework should allow lawyers to develop sound "instincts" about interstitial rules with which they may be unfamiliar. Furthermore, those aspects of landlord-tenant law most in need of reform can be seen as inconsistent with its fundamental conceptions. "Instincts" about these aspects may likewise develop; a visceral sense of injustice need not be the lone claim for reform. Change can be seen to promote, not derogate, the logical coherence of the law.
Keywords: Landlord & amp; tenant